Supporting Business Model Generation with Augmented Reality - Gräßler, Iris; Grewe, Benedikt; Kramer, Hendrik; Pottebaum, Jens (LUT Scientific and Expertise Publications)
Workshops on business model generation lead to collaborative work phases and discussions on business models. Therefore, tools such as the Business Model Canvas are used, typically filled with sticky notes. Generated content needs to be digitized in a time-consuming manual follow-up as part of the documentation and basis for a further use of the results in the company. In addition, there are challenges, such as decentralized work and digital workshop formats. Augmented Reality offers a way to reduce the digitization effort and enables decentralized work. In this research, the potentials of the use of AR technology in workshops on business model generation is investigated. Therefore, functions are implemented and evaluated in a demonstrator that reduces digitization effort and enable distributed work.
Keywords: business model generation; augmented reality; workshop; collaborative work; digitization; AR-supported workshop concept; immersive technologies; decentralized work; business model canvas

„Sie sind doch eine Medienklasse!“ - Caruso, Carina; Reis, Oliver (Österreichische Religionspädagogische Forum)
Ausgehend von Ergebnissen zur Mediennutzung und Ausführungen zur Medienkompetenz fokussiert der Beitrag digitale Praktiken im Religionsunterricht. Zur Analyse der mit der Digitalisierung verbundenen Transformation digitaler Praktiken wird die Akteur-Netzwerk-Theorie dargestellt sowie die Begriffe Digitalisierung und Digitalität definiert. Anhand einer Vignette (dichte Beschreibung) wird der Frage nachgegangen, wie sich Lehrkräfte auf Herausforderungen von Digitalität einlassen (können), inwiefern sie digitale Praktiken eröffnen und inwiefern diese mit traditionellen Praktiken verbunden sind.
Keywords: Digitale Praktiken; Digitalisierung; Medienkompetenz; Professionalisierung; Religionsunterricht / digital practices; digitization; digital literacy; teachers' professional development; religious education